Integrating and differentiating meanings in tweeting about the fifth Intergovernmental Panel on Climate Change (IPCC) report - Kim Holmberg; Iina Hellsten (First Monday, 2022)
The publication of the fifth Intergovernmental Panel on Climate Change (IPCC) Working Group 1 report in September 2013 was highly debated on Twitter. In this paper we focused on tweets that mention “IPCC”, and in particular the content and sentiment of the tweets sent by tweeters that were identified as unconvinced or as convinced towards the scientific basis of global warming. Our results indicate that the content and sentiment of those convinced reflect mainly information sharing activities instead of expressing opinions or participation in the debate. Climate change science is, however, challenged by some unconvinced tweeters who tend to use more negative words in their tweets. Our theoretical contribution is on the processes of meaning making around the IPCC report in relation to different groups of tweeters. We identify how certain words may be given different meanings by different groups, and how certain words have a differentiating function between the groups and integrating function within the groups. Our results increase our knowledge about the content of climate change debate in social media and on Twitter in particularly and contribute to research interested in how words function as differentiating and integrating meanings between and within social groups.